2019
DOI: 10.2196/13543
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Mobile Phone App and Telephone Coaching Survivorship Care Planning Program Among Spanish-Speaking Breast Cancer Survivors

Abstract: Background Spanish-speaking Latina breast cancer survivors experience disparities in knowledge of breast cancer survivorship care, psychosocial health, lifestyle risk factors, and symptoms compared with their white counterparts. Survivorship care planning programs (SCPPs) could help these women receive optimal follow-up care and manage their condition. Objective This study aimed to evaluate the feasibility, acceptability, and preliminary efficacy of a culturally and lin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(96 citation statements)
references
References 38 publications
3
93
0
Order By: Relevance
“…However, due to the few culturally adapted web-based interventions for patients with cancer, evaluation of the usage of these apps among minority patients has not been well-studied. The Nuevo Amanecer smartphone app for Latina breast cancer survivors, for example, is a culturally tailored smartphone app for Latina breast cancer survivors, which focuses on physical activity promotion [ 56 ]. Results from the Nuevo Amanecer feasibility trial revealed that women checked their physical activity tracking 4-6 times per week but click level data and total minutes spent engaging in the smartphone app were not reported as part of the study findings [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the few culturally adapted web-based interventions for patients with cancer, evaluation of the usage of these apps among minority patients has not been well-studied. The Nuevo Amanecer smartphone app for Latina breast cancer survivors, for example, is a culturally tailored smartphone app for Latina breast cancer survivors, which focuses on physical activity promotion [ 56 ]. Results from the Nuevo Amanecer feasibility trial revealed that women checked their physical activity tracking 4-6 times per week but click level data and total minutes spent engaging in the smartphone app were not reported as part of the study findings [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to adding wearable sensors, results collected via the symptom questionnaires could be confronted with the collected vital signs. Nápoles et al [27] presented a solution where a commercial-grade activity tracker was used together with the app to monitor and display progress toward a personalized daily steps goal.…”
Section: Collection Of Patient Data In Their Home Environment Using Smentioning
confidence: 99%
“…A systematic review of these studies [ 27 ] has shown that the use of SCPs has resulted in high levels of cancer survivor satisfaction, high levels of survivor perception that SCPs enhanced communication between providers, and variable levels of distress [ 27 , 28 ]. Increasing evidence points to the benefits and efficacy of survivorship care plans in reducing fatigue and distress, and improving long-term physical health and emotional well-being, physician-patient communication, patient experiences, and knowledge of recommended follow-up care [ 29 , 30 ]. SCPs therefore provide an opportunity to engage survivors in their health care, while also capturing meaningful treatment-related outcomes to use as basis for making informed decisions [ 31 ].…”
Section: Introductionmentioning
confidence: 99%